The transnational lyric community of Soviet unofficial music under late socialism - Bullock, PR (ICI Berlin Press, 2024)
Despite the seeming liberalism of Khrushchev’s ‘Thaw’, limitations were still placed on the Soviet arts, and the era witnessed the emergence of a parallel form of underground or unofficial culture. This essay considers a number of vocal works by composers, including Gubaidulina and Schnittke, who experimented with a cosmopolitan range of literary texts, as well as with a more radical musical language. In doing so, these composers not only established a lyric community at home but also engaged with their counterparts in avant-garde circles in Western Europe.